FAST PYROLYSIS OF PADDY HUSK USING ZEOLITIC MATERIAL FOR BIOOIL AND BIOCHAR PRODUCTION - NAQVI, SALMAN RAZA (2015)
The present research focuses on non-catalytic and catalytic fust pyrolysis of a Malaysian crop residue (paddy husk). This biomass was selected due to their abundant quantity in the country, the current inefficient recycling methods, and the little availability of the decomposition data from few published studies. The present study used catalyst in the fust pyrolysis process to explore the deoxygenation mechanism and reaction network of value-added compounds production by utilizing palm kernel shell as the feedstock.